Rapid ice-marginal lake growth in Alaska driven by glacier retreat through bed overdeepenings - Daniel McGrath; Louis Sass; William H. Armstrong; Caitlyn Florentine; Scott W. McCoy (Proceedings of the National Academy of Sciences, 2026)
The number and cumulative area of ice-marginal lakes have expanded globally in recent decades, with many lakes residing in glacier-bed overdeepenings, which are subglacial basins formed through preferential glacial erosion. However, current lake expansion rates, key drivers of expansion, and maximum future lake extents are poorly quantified. This is notable because glacial lakes pose hazards, alter hydrologic and ecological systems, and, in some cases, accelerate glacier flow and retreat. Here, we quantify recent ice-marginal lake growth and use existing ice thickness and topographic data to map glacier-bed overdeepenings in Alaska as a predictor of recent and future locations of lake growth. Ice-marginal lakes in the region grew by +156 km 2 (26 km 2 y −1 ) between 2018 and 2024, representing a 50% increase relative to the 2009–2018 rate. Eighty percent of lake growth since 2018 occurred in mapped glacier-bed overdeepenings. Approximately 4,250 km 2 (2,966 to 5,503 km 2 accounting for ± ice thickness uncertainty) of the overdeepened area is connected to an ice-marginal lake, indicating the potential for more than fourfold lake growth of existing lakes as glaciers retreat. An additional 14,500 km 2 (12,469 to 17,134 km 2 ) of remaining glacier area resides on glacier-bed overdeepenings not connected to existing lakes, highlighting the potential for substantial new lake development. Velocities from lake-terminating glaciers show clear passive and dynamic endmembers on a continuum of glacier–lake coupling. Glaciers with ice-marginal lakes thinned 23 to 54% more than glaciers of similar area without lakes, underscoring the critical importance of dynamic glacier–lake coupling on the evolution of glaciers in Alaska.